Of Rajuk and demasculinization. Examining class inequality and gender representations in Hussain Haniff’s Hang Jebat (1961) - Muhamad Farid Abdul Rahman; Mahyuddin Ahmad; Lee, Adrian Yuen Beng (Penerbit Universiti Kebangsaan Malaysia, 2020)
During the Golden Age of Malay cinema, Hussain Haniff was a prolific filmmaker who made 12 films within a period of five years. Started as an extra, escalated to editor, Hussain Haniff’s films mostly questioned the powers advocating the subject of rebellion and class injustice. Known as a rebel with modernist approaches, Hussain Haniff made films with rebellion being the theme within its narratives. This can be seen in his first directorial debut Hang Jebat (1961) that tells the story of how the warrior Hang Jebat stood up for his comrade Hang Tuah who was unjustly sent to the gallows. Hang Jebat in defying the orders of the Sultan and thinking that Hang Tuah had been executed, went into a fit of rage and as an act of rebellion ran amok while killing several villagers. In the Malay culture and Malay purbawara films, this treasonous act of rebellion known as “durhaka” is caused by an expression of “rajuk” – the sulk, or “merajuk” – the act of sulking, and occurs when a servant or warrior rebels against the act of injustice of his master. This paper aims to discuss the act of merajuk which often stereotyped as a feminine trait but in Hang Jebat it can be understood as a form of rebellion against feudalism and can be further attributed to understanding issues related to marginalisation and class oppression. Through an intertextual study of this film, this paper unravels how the rajuk of Hang Jebat represents an act of rebellion that challenges class inequality and gender representations. This article analyses rajuk in two main focuses; firstly on how explosive rajuk which is an allegory to the anti-feudal nature is expressed by Hang Jebat and how rajuk resulted an implication in his more feminine character compare to his rebel character at the beginning of this film.